A Comparison of the Internationalisation Strategies of British Consultant and Contractor Engineering Firms - Gandhi, Mohan (2017)
This study explored the factors affecting Internationalisation of large British engineering firms. Phone interviews with experienced knowledge-rich engineers identified stark differences in internationalisation strategies between contractors and consultants. Internationalisation literature was cross analysed with the empirical findings of this study, and gaps in the literature were identified for contractors and consultants respectively. It is hoped this critical analysis of the construction engineering field both aids manager decision making and illuminates an otherwise under-researched field of academia.